Factors that influence alcohol consumption among university students: a case study of Midlands State University - Rushwaya, Kudzai Jonathan (Midlands State University, 2018)
The use and abuse of alcohol has been high among Zimbabweans in general compared to other African countries and this has trickled down to university students in Zimbabwe .This study investigates on the factors that influence alcohol consumption of university students paying attention to the Midlands State University. Primary data was used to carry out this research and a probit regression model was used to carrying out the regression. STATA software was used to make the estimations. Empirics show that factors such gender, the number of friends who consume alcohol, the smoking status of the individual and family influences increase the probability of a young person consuming alcohol. To reduce the prevalence of alcohol consumption among university students, universities should roll out education campaigns to their students informing them of the health and social consequences of alcohol use and the effects of alcohol abuse. The findings of this research showed that smokers are more likely to consume alcohol than none smokers and as a result of this finding, it would be recommended that further studies be carried out on the impact that smoking has on drug use by university students. The findings also showed that gender was an insignificant variable, bearing this in mind it would be recommended that further studies be carried out to establish gender no longer is a significant variable bearing in mind the findings brought forward by Chambwe et al (1983) that showed that female university students in Zimbabwe were less likely to consume alcohol than their male counterparts